AN ANALYSIS OF CONTINUANCE INTENTION ON THE DISNEY+ PLATFORM USING THE SOR AND ECT MODELS - Davin, Hans; Ariyanti, Maya (UTSAHA: Journal of Entrepreneurship, 2025)
The development of the internet has disrupted many industries, particularly the media and entertainment sectors. People’s habits have shifted from traditional television to streaming services. One of the most popular streaming platforms in Indonesia is Disney+, which holds the second-largest market share in the country. However, Disney+ is currently facing a decline in user numbers, driven by a range of operational issues and controversies. This study aims to identify the factors influencing users’ intention to continue using Disney+, utilizing the SOR (Stimulus-Organism-Response) and ECT (Expectation Confirmation Theory) models. Data were collected through a questionnaire, yielding 402 valid responses from active Disney+ users. A quantitative research approach was employed, utilizing IPMA (Importance–Performance Map Analysis) as an extension of SEM-PLS (Structural Equation Modeling – Partial Least Squares) to identify the factors that exert the most significant influence and demonstrate high performance in shaping continued usage intention. The IPMA results indicate that entertainment and attitude are variables with a substantial impact on continued usage intention but exhibit low performance. Therefore, it is recommended that Disney+ allocate its resources to improve these two areas. On the other hand, the variable hedonic value demonstrates both high influence and high performance, suggesting that users’ hedonic experience must be consistently maintained to ensure their sustained interest in using the Disney+ platform.